Integritas Notaris Sebagai Pejabat Pembuat Akta Autentik dalam Undang-Undang Jabatan Notaris - Wahyu Satya Wibowo; Johni Najwan; Firdaus Abu Bakar (Recital Review, 2022)
Notaries as public officials who have the authority to make authentic deeds, in carrying out their duties are also attached to obligations that must be obeyed, because these obligations are something that must be carried out. Notaries are obliged to act honestly, thoroughly, independently, impartially and protect the interests of the parties involved in legal actions. The notary's obligations are included in the obligations to the client. Notaries as public officials are really required to have integrity. Integrity is the unity or consistency between heart, speech and action. A notary must: 1) have moral integrity, 2) a notary must be honest with his clients and himself (intellectual honesty), 3) be aware of the limits of his authority. Without or lack of integrity of a notary in carrying out his office, he will be very vulnerable to carry out manipulative, corruptive, collusive, dishonest/pure actions, conspiracy/secret approval, and many other negative actions. The notary is required to be responsible for the deed he has made. If the deed that was made turns out to be a dispute later on, the thing that needs to be questioned is whether this deed was the fault of the notary or the fault of the parties who did not want to be honest in giving their statements before a notary or whether there was an agreement between the two parties facing it. If the deed issued by a notary contains legal defects that occur due to the notary's error, either due to his negligence or because of the notary's own intention, then the notary must provide accountability. Violation of the Notary's Code of Ethics by a Notary may be subject to civil sanctions, administrative sanctions, and criminal sanctions. Abstrak Notaris selaku pejabat umum yang mempunyai kewenangan membuat akta otentik, dalam menjalankan tugasnya melekat pula kewajiban yang harus dipatuhi, karena kewajiban tersebut merupakan sesuatu yang harus dilaksanakan. Notaris berkewajiban bertindak jujur, seksama, mandiri, tidak berpihak dan menjaga kepentingan pihak yang terkait dalam perbuatan hukum. Kewajiban notaris tersebut termasuk ke dalam kewajiban terhadap klien. Notaris sebagai pejabat umum sungguh dituntut memiliki integritas. Integritas merupakan kesatupaduan atau konsistensi antara hati, ucapan dan tindakan. Notaris harus: 1) mempunyai integritas moral, 2) seorang Notaris harus jujur terhadap klien maupun dirinya sendiri (kejujuran intelektual), 3) sadar akan batas-batas kewenangannya. Tanpa atau kurangnya integritas notaris dalam menjalankan jabatannya, maka akan rentan sekali untuk melakukan tindakan-tindakan manipulatif, koruptif, kolutif, tidak jujur/murni, sekongkolan/persetujuan rahasia, dan masih banyak lagi tindakan negatif lainnya. Notaris dituntut untuk bertanggung jawab terhadap akta yang telah dibuatnya. Apabila akta yang dibuat ternyata dibelakang hari menimbulkan sengketa, maka hal yang perlu dipertanyakan adalah apakah akta ini merupakan kesalahan notaris atau kesalahan para pihak yang tidak mau jujur dalam memberikan keterangannya dihadapan notaris atau terdapatnya kesepakatan kedua belah pihak yang menghadap. Jika akta yang diterbitkan notaris mengandung cacat hukum yang terjadi karena kesalahan notaris, baik karena kelalaiannya maupun karena kesengajaan notaris itu sendiri, maka Notaris harus memberikan pertanggung jawaban. Pelanggaran Kode Etik Notaris yang dilakukan Notaris dapat dikenakan sanksi perdata, sanksi administrasi, dan sanksi pidana.